2014
DOI: 10.1016/j.jcrs.2014.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of suction on macular and retinal nerve fiber layer thickness during femtosecond lenticule extraction and femtosecond laser–assisted laser in situ keratomileusis

Abstract: Suction had no significant clinical effects on the macular thickness and retinal nerve fiber layer during femtosecond lenticule extraction or femtosecond laser-assisted LASIK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
26
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 19 publications
3
26
0
4
Order By: Relevance
“…In previous LASIK studies, MT was observed thickened [9], or total macular volume increased [17]. 1 day after surgery, all parameters returned to the baseline [18], and more extended observation did not see any signi cant changes [19]. While in our research, MT decreased after surgery, but GCL was unchanged.…”
Section: Discussionsupporting
confidence: 44%
“…In previous LASIK studies, MT was observed thickened [9], or total macular volume increased [17]. 1 day after surgery, all parameters returned to the baseline [18], and more extended observation did not see any signi cant changes [19]. While in our research, MT decreased after surgery, but GCL was unchanged.…”
Section: Discussionsupporting
confidence: 44%
“…13,14 Zivkovic et al 15 reported no significant changes in the thickness of the ganglion cell--inner plexiform layer after microkeratome assisted LASIK surgery. Zhang et al 7 reported no significant change in the thickness of the nerve fiber layer and ganglion cell complex after femtosecond laser-assisted LASIK surgery. As a result of this study, which evaluated the GCT with SD-OCT in the early period after femtosecond laser-assisted LASIK surgery, it was observed that there was no significant change in GCT and NFT values similar to the literature, and results correlated with CMT.…”
Section: Discussionmentioning
confidence: 99%
“…Данный метод обладает большей точностью, высокой повторяемостью и малой вариабельностью получаемых результатов [25][26][27]. При его использовании в работах, посвященных сравнению способов формирования роговичного клапана (микрокератомом или фемтолазером) при проведении операции ЛАЗИК, стойких изменений ПСНВС выявлено не было [7,10]. Лишь непосредственно после вмешательства (через 30 мин) обнаруживались истончение ПСНВС и утолщение фовеа, которые носили кратковременный характер и уже на следующий день после операции не определялись [10].…”
Section: Discussionunclassified
“…Другой вопрос о возможном влиянии изменений рефракции роговицы на параметры ПСНВС не был решен в достаточной степени, так как в большинстве рассмотренных выше исследований близорукость в среднем была от (-)3 до (-)5 дптр, достигая (-)5,46 -(-)6,43 только в двух работах [10,13]. По-видимому, при относительно небольшом рефракционном эффекте сложно ожидать существенных изменений параметров ОКТ.…”
Section: Discussionunclassified
See 1 more Smart Citation